2014
DOI: 10.3233/jvr-140705
|View full text |Cite
|
Sign up to set email alerts
|

Social-cognitive predictors of readiness to use evidence-based practice: A survey of state vocational rehabilitation counselors

Abstract: Evidence-based practice (EBP) is receiving increased attention from vocational rehabilitation (VR) professionals as the demand for accountability in rehabilitation and healthcare systems expands. The purpose of the current study was to determine the level of understanding VR professionals have of EBP with specific attention to perceived self-efficacy, outcome expectancy, barriers, and readiness to use evidence in current practice. Data were collected from 396 rehabilitation counselors, who were recruited from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 14 publications
5
13
0
Order By: Relevance
“…With the exception of a subgroup of counselors who disagreed with the implementation of EBP in rehabilitation counseling practice, rehabilitation counselors were generally supportive of the use of EBP in rehabilitation, which is consistent with findings from the previous three quantitative survey studies (Bezyak et al, 2010;Graham et al, 2013;Tansey et al, 2014). However, rehabilitation counselors in the current study provided more detailed descriptions of the specific barriers that preclude the actual use of EBP in rehabilitation counseling practice.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…With the exception of a subgroup of counselors who disagreed with the implementation of EBP in rehabilitation counseling practice, rehabilitation counselors were generally supportive of the use of EBP in rehabilitation, which is consistent with findings from the previous three quantitative survey studies (Bezyak et al, 2010;Graham et al, 2013;Tansey et al, 2014). However, rehabilitation counselors in the current study provided more detailed descriptions of the specific barriers that preclude the actual use of EBP in rehabilitation counseling practice.…”
Section: Discussionsupporting
confidence: 87%
“…A majority of rehabilitation counselors in this study and others indicated that they did not have sufficient skills and knowledge to effectively implement EBP in daily practice (Bezyak et al, 2010;Tansey et al, 2014;Yaeda, Iwanaga, Fujikawa, & Bezyak, 2015). To narrow this gap in knowledge and implementation, rehabilitation educators, researchers, and practitioners must all work together to assure that EBP information and materials are accessible and useful to professionals in the provision of rehabilitation services.…”
Section: Knowledge Translationmentioning
confidence: 92%
See 2 more Smart Citations
“…For example, VR counselors may lack clinical judgment skills if they are relatively new, or they may have reduced competence in this skill when facing highly complex situations (Austin, 2018). Furthermore, VR counselors often face challenges in integrating EBP in VR settings (Tansey et al, 2014). Within this context, many VR counselors will find it difficult to individualize high quality, evidence-based services to each VR consumer.…”
mentioning
confidence: 99%